The Pathways to the First Contact with Mental Health Services among Patients with Schizophrenia in Lagos, Nigeria. (31st December 2013) - Adeosun, Increase Ibukun; Adegbohun, Abosede Adekeji; Adewumi, Tomilola Adejoke; Jeje, Oyetayo O.
Abstract : There is increasing evidence that delay in the commencement of treatment, following the onset of schizophrenia, may be related to the pathways patients navigate before accessing mental health care. Therefore, insight into the pattern and correlates of pathways to mental care of patients with schizophrenia may inform interventions that could fast track their contact with mental health professionals and reduce the duration of untreated psychosis. This study assessed the pathways to mental health care among patients with schizophrenia (n = 138 ), at their first contact with mental health services at the Federal Neuro-Psychiatric Hospital Yaba Lagos, Nigeria. Traditional and religious healers were the first contact for the majority (69%) of the patients. Service users who first contacted nonorthodox healers made a greater number of contacts in the course of seeking help, eventuating in a longer duration of untreated psychosis (P < 0.001 ). However, the delay between the onset of psychosis and contact with the first point of care was shorter in patients who patronized nonorthodox practitioners. The findings suggest that collaboration between orthodox and nonorthodox health services could facilitate the contact of patients with schizophrenia with appropriate treatment, thereby reducing the duration of untreated psychosis. The need for public mental health education is also indicated.